Quantitative Study of the Effectiveness of Birthing Ball Exercises on Labor Pain and Self-Efficacy During Childbirth at the Baamang Community Health Center 1 - Marlina Diah Puji Rahayu (Master of Public Health Program Universitas STRADA Indonesia, 2022)
Background: Many women in labor want to avoid labor pain by minimizing the use of pharmacological methods. birthing ball Physically beneficial so it can be used during pregnancy and childbirth. In this case, birthing ball optimal positioning of the mother's body and reduction of pain during uterine contractions give rise to unusual movements. The underlying reason for practicing birthing ball can work effectively in childbirth. The aim of this research is to analyze the effectiveness of exercise birthing ball on labor pain and self-efficacy during labor. Method: Based on the research location, it is clinical research and there are treatments in the research. Based on the data source, it is primary research. This research is included in the Pre Experimental type of research with a pretest and posttest design. This research was conducted in the Maternity Room of Baamang 1 Health Center. Results: The results of the study showed that 58 percent of mothers experienced mild pain before the birthing ball exercise at the Baamang I Community Health Center, 33 percent of mothers experienced moderate pain and 10 percent of mothers experienced severe pain. And after doing it, as many as 58 percent of mothers experience no pain, 42 percent of mothers experienced mild pain. This is all because the mother understands and wants to follow the directions given by the researcher. Analysis: After testing Wilcoxon earned value Asymp.Sig. (2-tailed) is worth 0.000. Because the value of 0.000 is smaller than 0.05 (0.000<0.05), it is concluded that